Model Pembelajaran Kooperatif Tipe Stad (Student Teams Achievement Division) Di SMP IT Muhammadiyah Takengon - Murthada Murthada; Seri Mughni Sulubara (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
Cooperative Type STAD (Student Teams Achievement Division) is a way of organizing and dividing tasks between students in groups where the teacher is only a facilitator who gives directions so that interactions between students can occur in achieving the goal of gaining knowledge. Cooperative learning is group work in which there are several elements where a teacher leads the dialogue of interaction between its members so that there is social interaction that makes it easier for students to receive material in a teaching and learning activity. The problem in this study is that student learning outcomes are still low and the teacher explains that there are still many students who are lazy to study, sleepy while attending lessons, there are students who do not pay attention when the teacher is explaining the lesson, there are students who are busy with their friends, and do not bring textbooks . This study uses a descriptive qualitative approach. The research subjects were IT Muhammadiyah Takengon First School Children (SMP) students. Data collection techniques in this study used observation to describe children's learning abilities. Data analysis techniques using data reduction, data presentation, and drawing conclusions. This research wants to know the main components of the Student Teams Achievement Division (STAD) Cooperative Learning model, the advantages and disadvantages of applying the STAD type cooperative learning model and the benefits of the STAD type learner model for SMP IT Muhammadiyah Takengon students in helping to increase their activeness. student learning so that they can solve problems in learning at school easily, creatively, independently and smoothly